2008
DOI: 10.1117/12.790415
|View full text |Cite
|
Sign up to set email alerts
|

Advances in edge sensors for the Thirty Meter Telescope primary mirror

Abstract: The out-of-plane degrees of freedom (piston, tip, and tilt) of each of the 492 segments in the Thirty Meter Telescope primary mirror will be actively controlled using three actuators per segment and two edge sensors along each intersegment gap. We address two important topics for this system: edge sensor design, and the correction of fabrication and installation errors.The primary mirror segments are passively constrained in the three lateral degrees of freedom. We evaluate the segment lateral motions due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The edge sensor (Mast et al 1983;Chanan et al 2004;Shelton et al 2008) includes two parts, the sensor body and the target (a plane mirror), as shown in Figure 1. The main body is composed of a light-transmitting part, a lightreceiving part, and a collimating lens.…”
Section: Working Principle Of the Edge Sensormentioning
confidence: 99%
“…The edge sensor (Mast et al 1983;Chanan et al 2004;Shelton et al 2008) includes two parts, the sensor body and the target (a plane mirror), as shown in Figure 1. The main body is composed of a light-transmitting part, a lightreceiving part, and a collimating lens.…”
Section: Working Principle Of the Edge Sensormentioning
confidence: 99%
“…A singular value decomposition of A hz has been useful in understanding the properties of this matrix [6]. The output signal from each sensor is a linear combination of a signal generated by a height change and a signal due to the change in dihedral angle (relative rotation about the shared segment edge) [8]. The relative sensitivity between these has units of length (i.e., m∕radian), and is denoted L eff ; (at Keck, L eff 55 mm corresponds to a physical moment arm).…”
Section: A Descriptionmentioning
confidence: 99%
“…Other than the effect of the unobservable torsion mode, the vector of in-plane motion w can be estimated from the gap measurements, and this used to estimate the shear at sensor locations [8]. This allows calibration of the sensor response to both gap and shear motion using only gap measurements, with errors due to the unobservable torsion mode, and due to the propagation of gap-measurement noise.…”
Section: Estimation Of In-plane Motionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the horizontal layout, the sensor is positioned parallel to the mirror surface along its edge, while in the vertical layout, it is placed perpendicular to the mirror. A typical example of the vertical layout is the edge sensor used in the TMT [10]. This design employs non-interlocking and non-moving parts to simplify segment replacement.…”
Section: Introductionmentioning
confidence: 99%